A method for geometric features equivalence to assess the thermal behavior in the selective laser melting process - Zhiqiang Yan; Junjie Wang; Wei Luo; Jizhuang Hui; Jingxiang Lv; Hao Zhang; Zhiguang Xu; Qingtao Liu (Journal of Materials Research and Technology, 2023)
Selective laser melting (SLM) is a common technique categorized as one of the metal Additive Manufacturing (AM) processes to efficiently manufacture complex geometries. However, due to the diversity and difficulty in quantification of part geometry, it is hard to investigate different geometry, which is highly vital to the part quality, on the thermal behavior (TB) in the SLM process to ensure the part forming rate. To tackle this problem, a geometry feature equivalence (GFE) method was proposed to divide the geometric features into permutations and combinations of different GF elements. Firstly, common elements and uncommon elements were defined, where the former represents the element with the same track length in each track and the letter means the element has various track length in each track. Then, a finite element model was established and verified based on experiments to investigate the influence of GF elements on all kinds of TB including temperature variation, temperature changing rate, molten pool dimensions and lifetime. Next, for common elements, single-track model was analyzed to obtain the influence of the track length on the TB, which showed that the peak value of temperature, heating rate and cooling rate are at the starting point, and then gradually become stable with the track length increasing. After that, multi-track model was established to investigate the effect of the track number on the TB, which represented that the maximum heating rate keeps declining, the maximum cooling rate of each track are almost same, and the molten pool width and depth increase with the track number increasing. Moreover, two uncommon elements were designed and studied to obtain its TB, which demonstrates that even though the track length is the same in each track, different arrangement will bring out various temperature evolution. Finally, a thin-wall ring was built and measured based on experiments to validate the effectiveness of the proposed method. The proposed method can contribute to the part designer to obtain the TB of arbitrary geometric feature in design phase and guide the part geometry design and optimization.